FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017 - Syachna Maheswari Putri, 15.05.52.0353; Maryono, Maryono (Students' Journal of Accounting and Banking, 2019)
This study aims to examine and analyze the factors that influence stock prices in property and real estate sector companies on the Indonesia Stock Exchange. The population used in this study are property and real estate sector companies that publish their financial statements in 2015-2017. The sampling technique uses purposive sampling with predetermined criteria, namely property and real estate sector companies listed on the Indonesia Stock Exchange, publishing financial statements, and presenting complete financial reports and stock price reports. The sample in this study were 157 companies in the property and real estate sector. The results of the study can be concluded that inflation has a negative and not significant effect on stock prices. Interest rates have a negative and insignificant effect. Price Book Value (PBV) has a positive and significant effect on stock prices. Return On Assets (ROA) has a positive and significant effect on stock prices.